Unlocking the public memory - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Unlocking the public memory'Unfortunately indigenous information, and therefore the accrued memory, tends not to be valued by its holders. They may either believe the experience is common knowledge or, at the other extreme, insist that culture...